FIRST NATIONS ON VIEW: CANADIAN MUSEUMS AND HYBRID REPRESENTATIONS OF CULTURE - Ashley, Susan (eTopia, 2005)
Museums are important public sites for the representation and authentication of history and heritage in Canadian society.The study of history and ethnographic museums allows important insights into issues of race, ethnicity and identity, and especially how the colonial legacy has shaped how Canadians see themselves. Museums are a supreme expression of imperialist Europe — publicly funded institutions devoted to colonial sensibilities. This includes vast halls set up to display the “booty” of war and conquest as well as the mounds of material evidence produced by scientific research and collecting. Museums of the 19th century were concerned with objects (and objectifying) and possessed a foundational purpose to define what was cultured or civilized (and what was not). Early exhibits emphasized purity of race, the progression of history and the sense that the “white” European race was the pinnacle of evolution. Museums defined, and continue to define and present who we are as nations or communities or cultures, and inevitably separate the we from everyone else out there (Bennett, 1995; Hooper-Greenhill,1999). By using exhibition as its form of communication, museums set up frozen instances in time and fixed them, unchangeable, as expert truth; there was no opportunity then to contest or even engage in dialogue. Objects displayed, in public, for audiences to gawk at or exclaim over. This very act of exhibition was spectacular in the Debordian sense: a representation, divorced from reality, is presented to and consumed by an undifferentiated audience.